Biological, environmental, and psychological stress and the human gut microbiome in healthy adults - Desiree R. Delgadillo; Jessica L. Borelli; Emeran A. Mayer; Jennifer S. Labus; Marie P. Cross; Sarah D. Pressman (Scientific Reports)
Abstract Emerging research suggests that the gut microbiome plays a crucial role in stress. We assess stress-microbiome associations in two samples of healthy adults across three stress domains (perceived stress, stressful life events, and biological stress /Respiratory Sinus Arrhythmia; RSA). Study 1 (n = 62; mean-age = 37.3 years; 68% female) and Study 2 (n = 74; mean-age = 41.6 years; female only) measured RSA during laboratory stressors and used 16S rRNA pyrosequencing to classify gut microbial composition from fecal samples. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States was used to predict functional pathways of metagenomes. Results showed differences in beta diversity between high and low stressful life events groups across both studies. Study 1 revealed differences in beta diversity between high and low RSA groups. In Study 1, the low perceived stress group was higher in alpha diversity than the high perceived stress group. Levels of Clostridium were negatively associated with RSA in Study 1 and levels Escherichia/Shigella were positively associated with perceived stress in Study 2. Associations between microbial functional pathways (L-lysine production and formaldehyde absorption) and RSA are discussed. Findings suggest that certain features of the gut microbiome are differentially associated with each stress domain.